Piperazine-promoted gold-catalyzed hydrogenation: the influence of capping ligands - Fiorio, Jhonatan L.; Barbosa, Eduardo C. M.; Kikuchi, Danielle K.; Camargo, Pedro H. C.; Rudolph, Matthias; Hashmi, A. Stephen K.; Rossi, Liane M. (Catalysis science & technology, 2020)
Gold nanoparticles (NPs) combined with Lewis bases, such as piperazine, were found to perform selective hydrogenation reactions via the heterolytic cleavage of H2. Since gold nanoparticles can be prepared by many different methodologies and using different capping ligands, in this study, we investigated the influence of capping ligands adsorbed on gold surfaces on the formation of the gold-ligand interface. Citrate (Citr), poly(vinyl alcohol) (PVA), polyvinylpyrrolidone (PVP), and oleylamine (Oley)-stabilized Au NPs were not activated by piperazine for the hydrogenation of alkynes, but the catalytic activity was greatly enhanced after removing the capping ligands from the gold surface by calcination at 400 °C and the subsequent adsorption of piperazine. Therefore, the capping ligand can limit the catalytic activity if not carefully removed, demonstrating the need of a cleaner surface for a ligand-metal cooperative effect in the activation of H2 for selective semihydrogenation of various alkynes under mild reaction conditions.
First published 06 Dec 2019
Gesehen am 23.03.2021